STRATEGI PERAN ISTRI DALAM MEMPERTAHANKAN KELUARGA DARI PERCERAIAN DI KOTA SURAKARTA - Nuraini, Azizah; Nurhadi, Nurhadi; Yuhastina, Yuhastina (Universitas Tanjungpura, 2022)
This research aims at determining the supporting factors which cause the wife to maintain the marriage after divorce and how the wife's role strategy in maintaining the family to minimize the amount of divorce in Surakarta. Divorce is seen as a failure of the husband and wife to keep the marriage together. This issue comes from their different awareness and acceptance of their duties and responsibilities within the family. This research applied a qualitative case study method. The result shows that several factors encourage the wife to maintain the marriage after divorce: getting to know each other's friends, getting her parents' blessing, knowing some husband's behaviors that she likes, and having children. The strategies used by the wife in maintaining the family to minimize divorce are: to apply self-awareness to relieve ego, create open communication between husband and children, have a separate home from parents, and implement religious and moral principles in the family.